A lower canal fill rate and unreestablished vertical femoral offset may increase the risk of the postoperative periprosthetic fractures after cementless bipolar hemiarthroplasty for femoral neck fractures in elderly patients. - Xiaoxiao Zhou; Houlin Ji; Jiajun Wu; Haixiao Chen; Yang Yang (PLoS ONE, 2023)
Background Periprosthetic fractures (PPFs) is one of the major causes of failure of hip arthroplasty with cementless stem; however, studies on the incidence and risk factors of PPFs after cementless hemiarthroplasty for femoral neck fractures (FNFs) are lacking. Methods This retrospective study included patients who underwent cementless bipolar hemiarthroplasty for displaced intracapsular FNFs. The demographic data were reviewed, Dorr classification was used to describe morphology of the femur, radiological parameters were measured including stem-shaft angle, canal fill ratio (CFR), canal flare index (CFI), morphologic cortical index (MCI), canal calcar ratio (CCR), and vertical and horizontal femoral offset. Results The sample comprised 10 men and 46 women (affected hip: left, 38; right, 18). The mean patient age was 82.82±10.61 (range, 69-93) years, and the mean hemiarthroplasty to PPFs time was 26.28±14.04 (range, 6.54-47.77) months. Seven (12.28%) patients had PPFs. A significant relationship was found between the incidence of PPF and CFR (p = 0.012), patients had a significantly smaller femoral stem CFR (0.76%±0.11%) than controls (0.85%±0.09%). The PPFs group had a significant shorter and unreestablished vertical femoral offset (p = 0.048). Conclusions A smaller femoral stem CFR associated with a potentially unacceptably high PPFs risk in uncemented hemiarthroplasty for displaced FNFs may result from mismatched prosthesis and bone dimensions in the elderly population, especially when accompanied by a poorly reestablished vertical femoral offset. With increasing evidence of the benefits of cemented fixation, a cemented stem for the treatment of displaced intracapsular FNFs is recommended for such a elderly frail population.